Dengue-associated hemophagocyticlymphohistiocytosis in an adult: A case report and literature review. Issue 8 (February 2017) - Chung, Sang Mi; Song, Joon Young; Kim, Wonshik; Choi, Min Joo; Jeon, Ji Ho; Kang, Seonghui; Jung, Eunju; Noh, Ji Yun; Cheong, Hee Jin; Kim, Woo Joo
Abstract: Background: Infection-associated hemophagocytic syndrome (IAHS) is potentially a fatal disease caused by systemic infection complicated by hemophagocyticlymphohistiocytosis (HLH). Here, we report a case of HLH associated with dengue hemorrhagic fever (DHF) after a trip to Thailand. Case summary: A 33-year-old healthy female patient presented with 3 days of fever, myalgia, and skin rash. Serotype 3 dengue virus was isolated. Clinical and laboratory findings fulfilled the criteria of HLH. After the initiation of corticosteroid therapy, the patient recovered and laboratory findings were normalized. Conclusion: It would be important to differentially diagnose dengue-associated HLH from severe DHF. Early recognition and initiation of steroid treatment would be crucial for the successful treatment of dengue fever complicated by HLH.